Factors Influencing Smallholder Dairy Farmers’ Choice of Milk Marketing Outlet in Nandi North District, Kenya - Bunde , A. O.; Mudaki , J. S.; Mwangi , M. N. (African Journal of Education,Science and Technology (AJEST), 2025)
Smallholder dairy farmers make up the bulk of milk producers in Kenya yet there is fragmented information on determinants of the choice of milk marketing outlet. The main objective of this study was to determine factors which influence smallholder dairy farmers‟ choice of milk marketing outlet in Nandi North District. Rational choice theory was employed and a conceptual framework developed to link the study variables. Survey research design was employed in this study. Simple random sampling was use d with a study sample size of 185 household heads. The study employed interview schedule as the data collection instrument. Descriptive and inferential statistics were used to analyze data and present the study result. Chi-square test was used to test the hypotheses with the level of significance set at 5 percent. The results indicated that there exist factors which influence smallholder dairy farmers‟ choice of milk marketing outlet in the district. The state of road infrastructure, ownership of means of t ransport and services offered by the milk chilling plants influences the choice of milk marketing outlet. The results revealed that smallholder dairy farmers look for both milk price and a market outlet offering other services. Farmers forego high milk prices in urban areas in order to access credit and farm inputs offered by the chilling plants. The study concluded that it is important to invest in rural infrastructure especially roads in order to reduce marketing cost. Moreover, there is huge potential in the farmer producer groups in marketing of farmers produce. The study recommended that the government needs to remove barriers inhibiting their functioning and increase their capacity by offering training. Further research should be carried out to come up with strategy to improve policy makers understanding of the dairy industry in Kenya